UNDERSTANDING ONLINE TEACHERPRENEURSHIP THROUGH THE PRISM OF SELLERS’ AND BUYERS’ EXPERIENCE ON TEACHERSLAB.KZ - Yeleussov, Adlet (Nazarbayev University Graduate School of Education, 2022)
The teacherpreneurship phenomenon is a comparatively new and under-researched concept in education. It has a hybrid nature expressed in combining teacher leadership with entrepreneurial approaches. Teacherpreneurship may expand teachers' opportunities and introduce new professional pathways for their development. The purpose of the current study was to explore how users of the online marketplace for educators understand this teacherpreneurship and the advantages and disadvantages of it. The study employed a mixed-method approach using an online survey and qualitative online interviews as the data collection tools. Overall, one hundred twenty-nine users of the Teacherslab.kz platform participated in the online survey, while three registered teacher-sellers took a part in the interviews. In addition, the research was guided by the teacher agency theoretical framework, which explains how teachers could participate in and lead educational changes and introduce innovations and reforms. The research revealed that the current understanding of teacherpreneurship is mainly related to its financial side and opportunities to generate additional income. Moreover, the study results indicated that teacherpreneurship is at the initial stage of development in the CIS region. In addition, teachers who practice teacherpreneurship mostly reported a positive attitude towards teacherpreneurship and considered it a beneficial approach for teachers. In conclusion, decision-makers, teachers, and education leaders will benefit from the study's recommendations on developing teacherpreneurship and be aware of possible implications. The research findings will help teachers and school leaders understand who teacherpreneurs are, as well as their practices, possible risks and challenges, and contributions to improving the field of education.
Keywords: Type of access: Open Access; teacherpreneurship; marketplace; teacher-sellers; teacher-buyers; Kazakhstan